Factors Affecting Small-Scale Broiler Chicken Farm Profitability and Challenges Faced by Farmers in Egyptian Rural - H. B. Gharib; M. A. El-Menawey; R. E. Hamouda (Faculty of Animal Science, Bogor Agricultural University, 2023)
This study was conducted in Al-Sharkia and El-Fayoum provinces, Egypt, and aimed to determine factors affecting small-scale broiler chicken farm profitability and challenges faced by broiler farmers in Egyptian rural. A stratified random sampling technique was applied to collect data from 200 individual small-scale broiler farmers randomly selected in two provinces, 100 from each province. Data were collected through semi-structured interviews with questionnaires and direct observation at the farm level. The log-linear regression model form of a flexible Cobb-Douglas production function was used to analyze factors affecting the profitability of small-scale broiler chicken farms. The results indicated that women (60%) were the majority of owned flocks. The average respondent farmer’s age was 41.98 years old. The majority of the small-scale broiler performance was low and medium performance. The coefficients of the value of experience, gender, education, labor type, extension, training, veterinary, credit, flock size, management interventions, marketing information, and the market price of live chickens were positive influences, while farmer age, feed cost, home consumption, and mortality rate negatively influence the broiler profitability. The major challenges faced by small-scale broiler producers to increase their profitability are poor feed quality and access to marketing, veterinary services and credit. Therefore, efficient feed resources, marketing and veterinary services should be implemented to support small-scale broiler producers.